Linking Nitrate and Dihydrogenphosphate Motifs with N,N',N"-Triisopropylguanidinium Cation: Syntheses and Structures of NO3– and H2PO4– Salts - F. Said, Farouq (Asian Journal of Chemistry, 2013)
The trisubstituted guanidine N,N',N"-triisopropylguanidine (TPG) reacts with ammonium nitrate in water and with phosphoric acid in THF to produce (TPGH)2(NO3)2(H2O) (1) and (TPGH)2(H2PO4)2(H3PO4) (2) salts. Compounds 1 and 2 were characterized by X-ray diffraction analysis and the two structures displayed two crystallographically unique cations. A complex hydrogen-bonding scheme operates in 1 between the guanidinium cation and nitrate anion via N–H···O and O–H···O synthons. The primary structure of 2 is the formation of dihydrogenphosphate anion chains along the c-axis direction through O–H···O synthon, which are triply-crossed by the 3-fold cations consolidating a 3-D structure. Compound 1 crystallized in the monoclinic space group P2(1)/n, where a = 16.841(5) Å, b = 9.122(3) Å, c = 19.926(6) Å, b = 95.041(6)º and compound 2 crystallized in the monoclinic system space group P2(1)/c with a = 16.542(2) Å, b = 10.8515(16) Å, c = 18.702(3) Å, b = 91.888º(3).